Molecular epidemiology of hepatitis B virus in primitive tribes of Odisha, eastern India - Dwibedi, Bhagirathi (Pathog Glob Health, 2014)
Background and objective: Among the indigenous population of India, Primitive Tribal Groups (PTGs) are vulnerable to various health related events and some of the PTGs are showing a decline in population associated with high mortality rates. The present study was undertaken to define the prevalence of Hepatitis B Virus (HBV) infection, its genetic characterization and possible risk factors for transmission in five PTGs in Odisha, India. Methods: Cross-sectional observational studies were carried out in the Lodha, Saora, Khadia, Mankidia, and Juanga tribes residing in different parts of Odisha between 2006 and 2010. Results: Hepatitis B surface antigen (HBsAg) prevalence was 0.8%, 0.9%, 0.9%, 3.7%, and 1.7% in Lodha, Saora, Khadia, Mankidia, and Juanga tribes, respectively. While 54.8% of seropositive (HBsAg) cases demonstrated HBV DNA, occult HBV infection was observed in 19.48% of cases. High viral load with detectable ‘e’ antigen was found in 29% of HBsAg-positive individuals. All HBV isolates (n = 17) were genotype D without pre-core mutants. Only 15.6% of HBV positive individuals had symptoms of hepatic disease, though none had severe manifestations. Multivariate analysis of the prevailing risk factors indicated that shaving by the village barber was significantly associated with HBV transmission in males. Tattooing was found to be significantly associated with females. Interpretation and conclusion: This is the first report on HBV infection in PTGs of Odisha that suggests a high potential for transmission of HBV infection in two PTGs (Mankidia and Juanga). It warrants early public health attention in tribal populations vulnerable to HBV infection.